Leaching mechanisms of heavy metals from fly ash stabilised soils. Issue 7 (July 2018) - Leelarungroj, Kittitat; Likitlersuang, Suched; Chompoorat, Thanakorn; Janjaroen, Dao
Fly ash is an industrial waste material that is repurposed as a soil stabiliser worldwide. In Thailand, many ground improvement projects utilise mixtures of cement and fly ash to stabilise weak soils. In this study, leaching mechanisms of arsenic, chromium, lead, and zinc from cement and fly ash stabilised soils were investigated in the laboratory. Leaching tests were performed, with different leachants and pH conditions, on cement and fly ash stabilised soils used for soil improvement in road embankment construction projects in Northern Thailand. The results suggested that chemical compounds (CaO and MgO) on fly ash surfaces can control the pH of the fly ash and soil leachant. The dissolution of chromium and zinc was found to be amphoteric and controlled by oxide minerals at a high or low pH. Arsenic leaching was found to be oxyanionic where AsO4 3- prevented the adsorption of arsenic onto the negatively charged fly ash surface. Different types of leachant also leached out in different amounts of heavy metals.